Transforming Space into Place: Navigation of Kathmandu’s Social Landscape in a Short Story - Thulung Rai, Nirnay (NPRC Journal of Multidisciplinary Research, 2025)
Background: This paper studies the relationship between identity, space, and place in a short story set in Kathmandu. By analyzing Ranjan Adiga's short story "High Heels," set in the urban social space of Kathmandu, this paper explores how a character who migrates to Kathmandu from rural areas experiences both the challenges of exclusion and opportunities for reinvention.Methods: This paper utilizes a qualitative methodology to perform a close textual analysis. Through close reading, this research scrutinizes the protagonist's experiences of exclusion and reinvention within Kathmandu's society. The study integrates theoretical frameworks from Henri Lefebvre and Yi-Fu Tuan to interpret the story and contextualize the findings within a larger discussion of place-making in an urban hub.Results: The results infer that Kathmandu has a dual nature; it can be a space of exclusion and a space for transformation. The protagonist, despite experiencing caste, gender, and religious discrimination, actively seeks to create a sense of belonging through her job, faith, and fashion choices.Conclusion: This paper concludes (implies) that urban life has transformative potential for marginalized individuals, where they can challenge societal constraints and forge their own sense of belonging.Novelty: This paper introduces a unique perspective on literary analysis, a topic seldom explored in Nepal, where space, place, and identity are rarely analyzed together. It analyzes the entanglements of these elements with individual identity and the sense of belonging within a spatial context. It also offers a novel approach that can pave the way for future literary analysis of literature that deals with identity, literature, and place in Nepal.